Dietary Plasticity in a Specialist Predator, the Gyrfalcon ( Falco rusticolus ): New Insights into Diet During Brood Rearing - Robinson, Bryce W.; Booms, Travis L.; Bechard, Marc J.; Anderson, David L. (ScholarWorks, 2019)
Climate and landscape change are expected to affect species’ distributions and interactions, with potentially harmful consequences for specialist predators. Availability of optimal prey can affect reproductive success in raptors, especially in the Arctic, where dramatic differences in prey availability occur both within and between years. However, behavioral responses of dietary specialist, resident predators such as Gyrfalcons (Falco rusticolus) to changes in prey availability remain poorly understood. To improve understanding of how climate-driven changes in prey availability may affect diet of avian predators in the Arctic, we characterized Gyrfalcon diet on the Seward Peninsula, Alaska, in 2014 and 2015 from images representing 2008 prey items obtained by motion-activated cameras at 20 nests.We documented two important dietary shifts: the proportion of ptarmigan (Willow Ptarmigan [Lagopus lagopus] and Rock Ptarmigan [L. muta]) in the diet declined throughout the brood-rearing period in both years, and also differed between years. In both cases, ptarmigan were replaced by Arctic ground squirrels (Urocitellus parryii) in the diet. Despite shifts in prey composition, dietary breadth did not change, which revealed a facultative shift in prey use in which Gyrfalcons relied on prey of large size rather than prey of a particular taxon. We describe previously undocumented prey-use patterns during Gyrfalcon breeding, specifically an interchange between two prey species that are keystones in tundra ecology. These results are important for informing predictive models of climate change and adaptive species management plans. Further study of the interchange between prey types described in this study can strengthen insight into key ecosystem processes, and the cause and effect of potential decoupling of predator-prey interactions.